Evaluation of blood chemical, lipids profile and immune response on broiler chicks fed with milk thistle (Silybum mari- anum L.) and thyme (Thymus vulgaris L.) seeds in south-eastern Iran (Veterinary Science Development, 2014)
This study was conducted to investigate the effects of supplementation of milk thistle seeds (MTS) and thyme seeds (TS) on blood chemical, lipid profile and immune response in broiler chicks. In this study, 160 one-day-old chicks (Ross 308) were allocated to four treatments with four replicates based on a completely randomized design in a 2×2 factorial arrangement. The treatment groups were (A) basal control diet, (B) basal diet with 0.2 g/kg of MTS, (C) basal diet with 0.2 g/kg of TS and (D) basal diet with 0.2 g/kg of MTS and 0.2 g/kg of TS. Birds fed the (D) supplemented treatment (MTS plus TS) had the greatest levels of total protein, 4.26±0.27 g/L; albumin, 2.21±0.02 g/L; globulin 2.28±0.23 g/L; and aspartate aminotransferase (AST) activity, 152.18±4.46 U/L than the control birds [group (A)] (P